Dual-camera endoscopic imaging probe combining simultaneous illumination of white-light and laser sources for near real-time monitoring of tissue features. (July 2022) - Fridman, Michael; Shemesh, David; Abookasis, David
Highlights: Multi-parametric dual-display endoscopic system for monitoring dynamic responses of biological tissues. Integrating oximetry principles, laser speckles imaging, morphological information and image fusion processing. Provide physicians with unique information without changing the current commercial endoscope. System validation was demonstrated in two models of tissue injury challenge. Due its robustness and straightforward implementation it can be used in a broad range of endoscopic procedures. Abstract: In this work, a dual-display endoscopic vision system was designed as a multi-parametric tool to monitor dynamic responses of biological tissues. The endoscope integrates oximetry principles, laser speckles imaging, and image fusion processing to simultaneously monitor hemodynamic and metabolic information with high spatial resolution. In addition, morphological changes of the tissue were evaluated using linear approximation to Rayleigh-MIE scattering over the visible range. The setup contains a white light source (QTH lamp), an NIR laser (810 nm), commercially available endoscope, high speed four position filter wheel, and two CCD cameras (color and monochromatic) for near real-time processing and display. Validation of the system was demonstrated in two models of tissue injury challenge, including a drug toxicity experiment conducted on a mouse model and the artery occlusion of a human finger. The experimental results illustrate the ability of our system to simultaneously map and temporally track changes in tissue parameters which has the potential to provide valuable insight into the physiological state of the tissue during endoscopic surgical procedures, making it attractive in the future for use in clinical practice and research applications.